2012
DOI: 10.12669/pjms.291.2385
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of ESBL producing Enterobacter cloacae among children

Abstract: Objective: The emergence of ESBL producing Enterobacter cloacae in clinical isolates is posing a serious threat for treating nosocomial infections. The aim of the study was to determine the frequency of extended spectrum β-lactamase (ESBL) producing Enterobacter cloacae and to compare the phenotypic methods used for the characterization of ESBL producing strains. Methodology: This cross sectional observational study was conducted during April 2011 to March 2012 at Microbiology department of The Children’s Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…was 12.73% which was different from the other results in Pakistan (50%, 14.93%) (21,22), Nigeria (37.5%) (10) and Pennsylvania, the USA (33.33%) (9).…”
Section: Discussioncontrasting
confidence: 67%
“…was 12.73% which was different from the other results in Pakistan (50%, 14.93%) (21,22), Nigeria (37.5%) (10) and Pennsylvania, the USA (33.33%) (9).…”
Section: Discussioncontrasting
confidence: 67%
“…E. coli strains have been found resistant to co-trimoxazole (63%), ampicillin, and tetracycline (87% each) in a different study 26 . Massive self-medication and indiscriminately advised antibacterial drugs without scientific investigations could result in multi-drug resistant Gram-negative pathogens, particularly against cephalosporins, aminoglycosides, and fluoroquinolones in the wound as well as in other infections 20,31,32 . The production of AmpC, extended-spectrum betalactamases, and imipenemases among the Gramnegative isolates explicit the resistance against expanded spectrum cephalosporins [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%
“…The test procedure is as follows: ceftazidime/clavulanate and cefotaxime/clavulanate discs, in comparison with ceftazidime and cefotaxime discs alone (Oxoid Ltd., Basingstoke, Unite Kingdom). According to the CLSI 2019 antimicrobial susceptibility testing standards [ 19 ], EPE was defined when an increase in a zone diameter ≥ 5 mm for either antibiotic together with clavulanate vs the zone diameter of the agent, and it is reported that the ESBL phenotype of other Enterobacteriaceae can also be determined by the same method as the above four Enterobacteriaceae [ 20 ]. The left were defined as non-ESBL-producing Enterobacteriaceae (NEPE).…”
Section: Methodsmentioning
confidence: 99%